Midpregnancy cordocentesis training of maternal-fetal medicine fellows - Tongprasert F. (2014)
Objective To describe systematic cordocentesis trainingamong maternal-fetal medicine (MFM) fellows. Methods During their 2-year training period, five MFMfellows, who had completed systematic model training, performed 1116 midpregnancy diagnostic cordocentesisprocedures (mean, 223 (range, 185-259) procedureseach) under expert supervision. The details of the procedureswere recorded prospectively. Multiple pregnanciesand those with fetal chromosomal or structural anomalieswere excluded from analysis. The outcome measuresincluded success rate, duration of the procedure, fetal lossand complications. Results Of the 1116 procedures performed, 184 wereexcluded because of fetal abnormalities; the remaining932 were available for analysis. Cordocentesis wasperformed on free-floating umbilical cord (79.3%) andat the placental insertion site (20.7%). There was animmediate complication of transient fetal bradycardiain 10% of cases. Individual success rates ranged from98.1 to 100% and the mean cumulative success ratehad plateaued by approximately 60 procedures. Theoverall fetal loss rate was 1.3%. The overall mean ± SD duration of successful procedures was 4.4 ± 4.7 min, individual mean durations ranging from 3.7 to5.9 min. Conclusions MFM fellows with systematic training areable to perform cordocentesis with very high successrates, and with an acceptable procedure-related fetal lossrate. An intensive course of preclinical training with themodel, and more than 60 procedures on patients undersupervision is recommended. Copyright © 2010 ISUOG. Published by John Wiley & Sons, Ltd.